PERAN PENYULUH DAN GAPOKTAN DALAM PENGGUNAAN MESIN PERTANIAN UNTUK USAHA TANI PADI DI DESA PULOSARI KECAMATAN KEBAKKRAMAT KABUPATEN KARANGANYAR - Khamid, Muh Nur; Suwarto, Suwarto; Wijaya, Mahendra (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2016)
The number of agricultural workers in Pulosari Village is sufficient, but many young people and communities choose to work outside the agricultural field. The availability of manpower for farming activities in Pulosari Village is low, so that agricultural machinery assistance is needed to achieve the planting target. Management of existing farming business namely tractor, Trans planter, Thresher, Power Weedier, Sprayer and Combine Harvester. The role of combined groups of farmers and counsellor in developing rice cultivation through introduction and supply of farming, can improve farmers skill so that the development of agricultural tools and machinery can be used by farmers and do not negatively affect the labour of farm laborers and positively affect the level of wage of labour. The research objectives are: to know the availability of man power, to know the management of rice farming and to know the role of Farmers Group Unions in realizing the independence of farmers in farming in Pulosari Village Kebakkramat District Karanganyar Regency.